Student's Perception of Offline and Online Learning in Writing Class at the University of Mataram - Mulyaningsih, Sukma; Aziz, Atri Dewi; Udin; Putera, Lalu Jaswadi (Journal of English Education Forum (JEEF), 2025)
This research aims at analyzing and describing, then finding out students’ perception of offline and online learning in writing class at the University of Mataram. The research method used is quantitative and qualitative method. 25 students are selected as the sample of this research from the population. The instruments of this research were questionnaires and interview. Online surveys were employed as research tools to get the data. These questionnaires were administered through a Google Form survey sheet and they were distributed via WhatsApp. The results of this research students have mixed opinions about the implementation of offline and online learning in writing class. Students also face challenges in learning English through offline and online methods, such as having trouble adjusting to new learning habits. The students’ perceptions toward offline and online learning in writing class at the University of Mataram split into 2 categories: students’ perception of offline and online learning and students' challenge experiences during offline and online learning in writing class at the University of Mataram. The majority of students support the implementation of offline and online learning in writing classes, with 32.16% agreeing and 29.76% remaining neutral. The bottom position is seated by the groups of students that oppose or do not support the implementation of offline and online learning in writing class with 11.44% of the total students. Thus, it can be concluded that the more students propose or support the implementation of offline and online learning in writing class.